THE EFFECTIVENESS OF USING PICTURE SERIES IN TEACHING WRITING RECOUNT TEXT FOR THE SEVENTH GRADE STUDENTS AT MTs MANBAUL ULUM MOJOPUROGEDE - Thoyyibatul Munifah; Lailatul Masruroh; Ahmad Thoyyib Shofi (J-Shelves of Indragiri (JSI), 2024)
The title of the research is The Effectiveness of Using Picture Series in Teaching Writing Recount Text for the Seventh Grade Students at Mts. Manbaul Ulum Mojopurogede. The problem of this research is to determine the significance of the effect of using the picture series in teaching writing recount texts for the seventh grade at MTs Manbaul Ulum Mojopurogede. The objective is to find out whether the picture series media is effective in teaching the writing of recount texts for the seventh grade at MTs Manbaul Ulum. The researcher uses the quantitative method by using a quasi-experimental research design. To collect the data, this research uses a pre-test, a treatment, and a post-test as the instruments, and the data was collected, processed, and the results were compared using a statistical test results table using the SPSS 26.0 application. The population and the sample of this research are all students in the seventh grade at MTs Manbaul Ulum in the academic year 2023-2024, of which there are 52 students.The result of this research shows that the use of picture series as a media to teach recount text writing skills can effectively increase students' writing skills, as confirmed by the t-test formula.